Exercise in the Treatment of Youth Substance Use Disorders: Review and Recommendations - More, Alissa; Jackson, Ben; Dimmock, James A.; Thornton, Ashleigh L.; Colthart, Allan; Furzer, Bonnie J. (Frontiers in Psychology, 2017)
Substance use disorders among youth represent a significant public health concern. It is well established that regular exercise provides important physical and mental health benefits; however, evidence for the role of exercise as an adjunct component within substance use disorder treatment is scarce. In this review, we identify factors associated with the development and persistence of substance use disorders among youth, identify current treatment modalities, and present evidence to support the efficacy of incorporating exercise participation during rehabilitation. We also provide a series of recommendations for future research that explores the feasibility and effectiveness of exercise participation as a complement to substance use disorder treatment among youth.